Production specialist performance appraisal form / Ahmad Azhari Mohamad Azman … [et al.] - Mohamad Azman, Ahmad Azhari; Roslan, Afini; Mohd Hosli, Nurin Khalida; Salehin, Nur Syahirah Liyana; Abd Azis, Noor Azreen Ain; Krishnan, Ramesh (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Performance appraisal forms which also known as performance review forms is a tool used by manager and human resources staffs to evaluate the employee’s performance in work organizations. Many work organizations still using manual performance appraisal forms and there are no sufficient information included in their performance appraisal forms. Due to this reason we propose an e-appraisal form which will include all important information needed to make a fair performance rating score for employees. This e-appraisal form was created electronically using the Microsoft Excel platform which is easier for the organization since the forms can make employees’ performance rating calculations automatically. Additionally, this e-appraisal form also has included many aspects that need to be taken into account in employee appraisal such as the workers competencies and personality criteria. This e-appraisal form is expected to improve the effectiveness of supervisors in conducting their subordinate’s performance. On the other hand employees also expected to benefits as they can monitor their performance level and respond to the comments as well as recommendations given by their supervisors. Keywords: performance appraisal, e-appraisal form, employee performance the organization since the forms can make employees’ performance rating calculations automatically. Additionally, this e-appraisal form also has included many aspects that need to be taken into account in employee appraisal such as the workers competencies and personality criteria. This e-appraisal form is expected to improve the effectiveness of supervisors in conducting their subordinate’s performance. On the other hand employees also expected to benefits as they can monitor their performance level and respond to the comments as well as recommendations given by their supervisors.